How the Quality of Long-Term Care Services Impacts Caring Relatives’ Well-Being in Austria - Hanzl, Lisa (Momentum Quarterly, 2022)
In a family-centered care regime like the Austrian one, informal caregivers’ well-being is central, especially in times of increased pressure due to the COVID-19 pandemic. This paper analyzes the connection between the quality of long-term care (LTC) services and informal caregivers’ well-being in Austria using a mixed methods approach. First, looking at data from the 2016 European Quality of Life Survey (EQLS), an OLS model shows that where the quality of LTC services is rated higher, individuals report higher life satisfaction, independent of their caring responsibilities. The most important explanatory factor for caregivers’ well-being is the usage of such services. However, it does not offer conclusive insights into how well-being is influenced. Therefore, I undertake a qualitative analysis via an online questionnaire in which 20 informal caregivers participated between March and April 2020. The survey was created using the capabilities approach and evaluated by means of thematic analysis. The main findings show that low-quality LTC services mainly reduce well-being due to the irregularity of said services, which disrupts the daily routine. High-quality LTC services, on the other hand, improve well-being allowing caregivers to share responsibilities.
Keywords: long-term care; caring relatives; well-being; mixed methods